Relación entre la densidad de la masa y la producción de corcho en montes alcornocales del sur de españa - Álvarez, E. Torres; González, G. Montero; Suárez, M. A.; Cámara, D. E. L. A.; TORRES ÁLVAREZ, E.; Montero González, G.; Suárez de la Cámara, M. A. (II Congreso Forestal Español, 1997)
In this paper the influence of cork-oak stand density on quantity and quality cork production is studied. Seventy five experimental plots were installed at Cortes de la Frontera (Málaga, Spain) cork-oak forests. Sorne stand and productive variables for different basal area were studied. The statistical analysis of the data permit to propose 20-25 m2!ha basal area as the optimum stand density
The following values have no corresponding Zotero field: periodical: II Congreso Forestal Español pub-location: Pamplona
Keywords: cork-oak; Quercus suber; silviculture; stand density